Adaptive Control-based synchronization of chaotic systems with uncertain parameters and its application - Hussain, Ola Jabbar; Tahir, Fadhil Rahma (Basrah Journal for Engineering Sciences, 2016)
This paper is concerned with performance on the widely used control technique: adaptive control for synchronization between two identical chaotic systems embedded in the Master and Slave. It is assumed that the parameters of slave system are unknown. The required stability condition is derived to ensure the stability of error dynamics. Adaptive control laws are designed using appropriate parameters estimation law. The system parameters are asymptotically synchronized; thus the slave parameters can be identified. As an application, the proposed scheme is applied to secure communication system. The information signal is transmitted and recovered on the basis of identification parameters also the system is tested under the consideration of the noisy channel. Finally, through Numerical simulation results, the proposed scheme was success in the communication application.